Revision of the Siobla formosana group (Hymenoptera: Tenthredinidae) - Niu, Gengyun; Wei, Meicai (Zootaxa, 2013)
14 species of the Siobla formosana species-group are revised. Three new species: Siobla jiangi Niu & Wei, sp. nov., S. parallela Niu & Wei, sp. nov., S. weiweii Niu & Wei, sp. nov. are described. Siobla rufipes Malaise, 1945 is a new synonym of S. atra Malaise, 1945. The males formerly assigned to S. atra belong to S. semipicta Malaise, 1945. The previously unknown female of Siobla rufopropodea Wei, 1998 is described. Lectotypes are designated for Siobla rufipes Malaise, 1945, Siobla atra Malaise, 1945 and Siobla semipicta Malaise, 1945. The previously described species are illustrated and partly redescribed. A key to species of the group is given. Distribution records of each species of the group except S. takeuchii are given.